Cumulative live birth rate in mild versus conventional stimulation in progestin-primed ovarian stimulation protocols for individuals with low prognosis - Zhang, Junwei; Du, Mingze; Zhang, Caihua; Wu, Yanli; Guan, Yichun (Frontiers in Endocrinology, 2023)
The purpose of this study was to evaluate the cumulative live birth rate (CLBR) of mild stimulation and conventional stimulation for the low-prognosis population undergoing PPOS protocols. Methods: This was a retrospective cohort study. We included women with a low prognosis. All women underwent PPOS protocols, and the starting gonadotropin (Gn) dose was 150 IU or 300 IU. The primary outcome measure was CLBR. The secondary outcome measures were the number of oocytes retrieved, number of 2PN oocytes and number of available embryos. Results: In total, 171 women with mild stimulation and 1810 women with conventional stimulation met the criteria. In the PSM model, 171 mild stimulation cycles were matched with 513 conventional stimulation cycles. The gonadotropin dosage in the mild stimulation group was significantly lower than that in the conventional stimulation group (878.6±1065.7 vs. 2854.7±821.0, P<0.001). The numbers of oocytes retrieved, 2PN oocytes, available embryos and high-quality embryos were also higher in the conventional stimulation group than in the mild stimulation group (P<0.05). There was no significant between-group difference in the cumulative clinical pregnancy rate (26.3% vs. 27.5%, P=0.77). The CLBR after mild stimulation was similar to that after conventional stimulation (21.1% vs. 22.0%, P=0.79). Conclusions: In our study, we found that the CLBRs of mild stimulation and